2022
DOI: 10.5430/jnep.v12n7p1
|View full text |Cite
|
Sign up to set email alerts
|

Theories used by nurses to promote patient safety practices: A scoping review

Abstract: Aim: To review available scientific evidence in the literature on theories that have been used to promote patient safety practices in the hospital environment.Methods: Design: A scoping review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews checklist. Method: the study was conducted between October and November 2020. The following databases were used to identify studies: Medline, Lilacs, BDENF, CINAHL, and Scielo Library. The following se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…9 SCT was used in the theory framework in nursing patient safety practice through educating programs about hand hygiene knowledge and attitudes among nursing students. 10 The findings demonstrated that the intervention could bolster nursing students' confidence and skills, often leading to heightened self-efficacy, which refers to personal factors affecting the patient safety practices of nurses. 11 Thus, SCT was adopted in this conceptual framework in this study.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 96%
“…9 SCT was used in the theory framework in nursing patient safety practice through educating programs about hand hygiene knowledge and attitudes among nursing students. 10 The findings demonstrated that the intervention could bolster nursing students' confidence and skills, often leading to heightened self-efficacy, which refers to personal factors affecting the patient safety practices of nurses. 11 Thus, SCT was adopted in this conceptual framework in this study.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 96%